The impact of an educational program on recognition, treatment and report of child abuse - Pietro Ferrara; Antonio Gatto; Nunzia Pia Manganelli; Francesca Ianniello; Maria Elisa Amodeo; Maria Amato; Ida Giardino; Antonio Chiaretti (BMC, 2017)
Abstract Background Pediatricians play a crucial role in the identification and management of child abuse and neglect (CAN) but they often don't have a formal specialized training. Methods We analysed retrospectively data about patients, 0 - 18 years of age, victims of CAN between 1 April 2005 and 30 April 2015. The aim of the study was to evaluate the effect of a multidisciplinary educational program, "CAN: prevention strategies, individuation and treatment", on the knowledge, case recognition, treatment and follow-up of physicians of Gemelli University Hospital in Rome, regarding physical, sexual abuse and neglect. This program, in 3 different editions biannually, respectively in May-July 2010, November-January 2012 and February-May 2014, was based on 4 sessions, each one of 2 days. Results Considering the number of victims of CAN between 2005 and 2015 we observed 66 cases of maltreatment. We divided the study population in 2 groups: group A, before the educational programs, patients evaluated from 1 April 2005 to 30 July 2010; group B, after the educational program from 1 August 2010 to 30 April 2015. We observed 23 children in group A and 43 children in group B with an improvement of 87%. Analyzing our data about sex, nationality, type of perpetrators, we found that: 37/66 (56%) of children were females compared to 29/66 (44%) males; 41/66 (62%) of children came from Italy compared to 25/66 (38%) of foreign children; 52/66 (79%) of the perpetrators of abuse were parents or family members compared to acquaintances 10/66 (15%) and to strangers 4/66 (6%). Conclusions Considering the prevalence of CAN, the need to develop clinically competent clinicians and the improving of residency education in child maltreatment is imperative. Improving the clinical skills of pediatricians to identify and evaluate CAN may lead to reduce morbidity and mortality of these children.